RAISING AWARENESS OF PLASTIC WASTE BY MAKING ECOBRICKS IN ELEMENTARY SCHOOLS - Ummu Kholifatul Khasanah; Siti Mayang Sari; Azadin Anhar (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
As one of the Adiwiyata schools in Banda Aceh city, SDN 27 Banda Aceh is very focused on waste management in the school environment. Teachers invite students to minimize the use of waste, especially plastic waste which takes a very long time to decompose. Teachers invite students to the Final Disposal Site (TPA) for waste located in Gampong Jawa, Banda Aceh City to see firsthand how workers at the TPA manage waste starting from sorting waste according to the types of waste and processing it into organic fertilizer, biogas, or waste that can be resold such as bottle waste, plastic waste, cardboard, cans, iron and others. In the Real Action activity, students collect waste in groups and then sort it according to the type of waste. The main focus of this project is on plastic waste. The plastic waste that has been collected is cleaned, dried and cut into small pieces and then put into plastic bottles until full and solid. This activity is known as Ecobrick. After all the bottles are full, they are glued, painted and covered with plywood or board on the top side to be used as a table and covered with cloth as a table mat to make it more attractive. The work that has been made is used as a table in the reading corner in the classroom.